Happiness With New Smile After Composite Filling in The Fractured Teeth - Dyah Ayu Retno Wulan; Istien Wardani; Annisa Listya Paramita; Yufita Fitriani; Yulie Emilda (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2023)
Background: A Fractured front teeth have an impact on children's psychology. Treating the front teeth with good aesthetics restores happiness. Dentists will try to restore fractured front teeth at a low cost will help the patient and family. Objective: #11 pulp necrosis accompanied by Ellis class III fracture, positive percussion test, positive bite test, and grade I mobility. Case: A 12th years old boy, visited pediatric dentistry clinic dr. Ramelan Naval Hospital Surabaya with his mother complaining that her child fell and broke his front teeth. And her child didn't want to go to school because not confident. Case management: Root Canal Treatment was restored with a composite using a palatal index with a layering technique supported by his insurance. Conclusion: The aesthetics of the teeth, especially the anterior teeth, is very important for the patient's confidence because they are visible when smiling, optimal support for children in the process of growth and development both physically and psychologically and selection of the type of treatment needs to consider the patient's finances while maintaining good quality